Obtenção de fibras cerâmicas ultrafinas à base de Nb₂O₅ para a fotoconversão gasosa de dióxido de carbono - Prado, Ana Carolina Figueiredo (Universidade Federal de São Carlos, 2021)
The increase in global warming rates is worrisome due to the harmful effects on different ecosystems. However, there is a need to reconcile these figures with the demand of industrial society for food, health, leisure, and energy production, which directly/ indirectly contribute to the increase in greenhouse gas emissions. Pollutants such as NOx, CO2, CH4, and others, significantly affect the lives of beings as a whole. One way to minimize these effects is to remove and reuse these pollutants from photocatalytic processes. In this sense, one of the promising materials for application in conversion is Nb2O5, due to its photocatalytic properties, abundance in Brazil, and low cost compared to usual catalysts. The present work aimed to develop a photocatalyst system based on ultrafine Nb2O5 fibers to convert CO2. To obtain the ceramic fibers, the electrospinning method was used, followed by heat treatment. The concentrations of the polymeric solutions and the heat treatment conditions were optimized. For the evaluation of the photocatalytic activity of Nb2O5 fibers in the conversion of CO2, a reactor monitored by gas chromatography was used to quantify the products generated. At the end, the stability of the system was evaluated in view of the number of reuse cycles. Furthermore, when varying the calcination temperature, it was observed that the temperature of 600°C for 2 h was the condition that made it possible to obtain homogeneous nanofibers with average diameters of 84 nm. It was confirmed that the Nb2O5 nanofibers converted CO2 mostly into CO and CH4 at less ratio, with values close to 8.5 μmol g-1 and 0.55 μmol g-1, respectively. In reuse tests, a decrease in CO production was identified until the end of the 4th cycle, whereas for methane these concentrations were not observed. Consequently, photocatalyst nanofibers based on Nb2O5 were obtained, which enabled the CO2 converting process to added value products CO and CH4.
Obtaining ultra-thin ceramic fibers based on Nb₂O₅ for gaseous carbon dioxide photoconversion
Keywords: Conversão de CO2; Fotocatálise; Eletrofiação; Nanofibras; Nb2O5; CO2 conversion; Photocatalysis; Electrospinning; Nanofibers; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA